Best Answer

f(x) = x6 - 3x

g(x) = x2 - 4

f(g(x)) = f(x2 - 4) = (x2 - 4)6 - 3(x2 - 4)

= (x2 - 4)6 - 3x2 - 12

= (x12 - 24x10 + 240x8 - 1280x6 + 3840x4 - 6144x2 + 4096) - 3x2 - 12

= x12 - 24x10 + 240x8 - 1280x6 + 3840x4 - 6147x2 + 4084

Q: What is F of g of x when f equals y to the 6th minus 3y and g equals t squared minus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(3y - 5)(y + 5)

6x - 4y

Y=-1

If you mean 3y+24 = y-12 then the value of y works out as -18

(4, -7)

Related questions

(3y - 5)(y + 5)

i think its 3y squared

7(3y-2)-(-4y+9)

It is: 3y(2y-3x) when factored

6x - 4y

#

2x+3y=13 3x-y=3 x=2

(3y2)4*3y2*3y2*3y2*3y2 = 38*y16 = 6561y16

3y squared - 2y = 1

Slope = 5/3 = 1.66...

Y=-1

The GCF is 3y^2.